The structure of modern cultural theory - Osborne, Thomas, 1964- (Manchester University Press ; Distributed exclusively in the USA by Palgrave Macmillan, 2008)
This book is about the claims of Cultural Theory as a particular kind of intellectual ethos or discipline. The book argues that Cultural Theory is best seen, at least in its?modern? form, as an ethical discipline. As such, it should be seen as a form of inquiry governed by the guiding idea of the cultivation of critical autonomy and, as such, is designed as much to change what we are in our relations to ourselves as to describe the world as it is in particular?positive? ways. The content of the book develops this argument through critical readings of three canonical writers, namely Theodor A.